Body image delationship with demographic variables in young adults - Miškinytė, A.; Bagdonas, A. (Psichologija, 2010)
This study is aimed to evaluate different attitudinal body image components that are characteristic specifically of youth Lithuanians. This kind of study is one of the first in this country. The article presents a brief review of recent studies concerning body image and points out that mostly separate aspects of body image are being reported on in the literature. Body image is a multidimensional phenomenon. Therefore, the aim of this study was to consider the attitudinal body image not in total, but in its different components and their relationship to gender, age and marital status. The study cohort comprised 419 students (1st to 6th year and residential doctors) of Vilnius University, Vilnius Pedagogical University, Vytautas Magnus University and Kaunas University of Medicine; of them, 78% were women and 22% men. The age of the respondents varied from 18 to 39 years (mean, 21.99 ± 3.46 years, men’s mean age 22.24 years (±3.87 years) and women’s 21.91 (±3.34 years). More than half of the respondents were single or separated (66,3% men and 64,8% women, respectively), more than one third reported having a girl/boy-friend, being married or living together with their partner. Women (28.8%) reported more often being married or living with partner than men (21.7%). The following methods of measuring different aspects of body image were used in this study: the Multidimensional Body-Self Relations Questionnaire – Appearance Scales (MBSRQ – AS), Appearance Schemas Inventory – Revised (ASI-R), Short Form of the Situational Inventory of Body Image Dysphoria (SIBID-S), Body Image Quality of Life Inventory (BIQLI). The results were follows: (1) body satisfaction is different for men and women: women are more concerned with their body weight, shape and some body parts (especially lower torso and their hair), they attend to and invest in their physical appearance more often than men; (2) younger men and women relate their self-worth with their looks more often than older men and women. Younger men are more-appearance oriented. Younger women report more dysfunctional attitudes towards their appearance, although they report a higher subjective quality of life than older women; (3) partnership in women is related with a better evaluation of one’s appearance, less dysfunctional attitudes towards their appearance and less negative emotions concerning their body. Partnership in men is related to a higher subjective quality of life; (4) American men and women in comparison with Lithuanian subjects report placing more importance on their looks, are more concerned with their body weight, they report more dysfunctional attitudes towards their bodies and report more body image dysphoria. American women report being overweight more often, are more often dissatisfied with different body parts and report lower subjective quality of life than Lithuanian women.